1986
DOI: 10.1007/bf00019775
|View full text |Cite
|
Sign up to set email alerts
|

On the stress singularity in steady-state transonic shear crack propagation

Abstract: The steady-state problem of a semi-infinite shear crack propagating with a velocity greater than the shear-wave velocity was considered. The crack was modeled by a straight cut which extended in its own plane under the action of in-plane shear stresses uniformly distributed over a segment of the crack lips. In this paper we were particularly interested in the stress singularity which was found to be different from that corresponding to the subsonic case. Complex variable methods have been employed exclusively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…if contact is giving way to separation--the strength of the singularity will be equal to or stronger than square-root, being described by the multiplier (x -b)-1/2-~. We note that an expanding crack [30,31] is equivalent to a receding contact region and therefore has the same asymptotic behaviour 3.…”
Section: Discussionmentioning
confidence: 86%
“…if contact is giving way to separation--the strength of the singularity will be equal to or stronger than square-root, being described by the multiplier (x -b)-1/2-~. We note that an expanding crack [30,31] is equivalent to a receding contact region and therefore has the same asymptotic behaviour 3.…”
Section: Discussionmentioning
confidence: 86%
“…In the course of this investigation, an integral equation formulation was developed for the steady-state problem of an indenter moving over a half-plane at constant speed, using the classical solution of Cole and Huth (1958) as a Green's function. However, the resulting equation exhibited different asymptotic behavior at the ends of the contact zone from other published solutions to elastodynamic crack and contact problems (see, e.g., Brock, 1977;Freund, 1979;Burridge et al, 1979;Georgiadis, 1986;Robinson and Thompson, 1974). Further investigation showed that this inconsistency was attributable to an error in the Cole/Huth solution in the transonic range.…”
Section: Introductionmentioning
confidence: 58%
“…Fung, 1965;Georgiadis, 1986;Barber, 1996;Brock and Rodgers, 1997) according to which a steady stress and displacement field is created in the medium w.r.t. an observer situated in a frame of reference attached to the moving load, if this source has been moving steadily for a sufficiently long time.…”
Section: à1 (K)mentioning
confidence: 99%